Through my eyes [compact disc, unabridged] - Delinsky, Barbara (Dreamscape Media, LLC, 2014)
Since her husband's death, Jill Moncreiff has lived alone in a small, coastal Maine town, pursuing her career as an artist. But her best friend is in trouble and needs legal advice. And that counsel comes in the form of the best lawyer Jill can find. Peter Hathaway is big city, big name and big money--everything Jill rejected years ago. She knows she needs his help, but she isn't prepared to like him. Nor does she expect to start imagining a new life filled with desire, family, and love.